In nomine dominae: notarial documents and women's lives in Genoese Chios (1348-1522) - Ravera, Chiara (2019)
The present study takes a gendered approach towards the notarial documents produced in the Greek island of Chios while it was under Genoese rule (1346-1566). For the first time these deeds are used to investigate women’s lives, focusing particularly on their contribution to the economy of the island and how their marital status influenced it.